Evaluasi Pelaksanaan Program Gerakan Literasi Sekolah Di Sekolah SMAN 1 Kualuh Selatan Labuhan Batu Utara - Muhammad Irvan; Lukmawati Lukmawati; Khadijah Pasaribu; Nindi Aulia Putri; Siddiq Permadi; Yuli Amelia (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2023)
Literacy is the ability to read and write. Even so, the notion of literacy can still be developed further, because literacy which only consists of reading, writing and arithmetic is now not enough, but must also include reading and writing as previously mentioned, numeracy literacy, scientific literacy, financial literacy, information and communication as well as cultural literacy and citizenship. This article aims to evaluate the implementation of the School Literacy Movement program at SMAN 1 Kualuh Selatan Labuhan Batu Utara. This type of research is descriptive evaluation research where data is collected mainly through surveys, namely interviews, observation and distribution of questionnaires to research subjects.